Destabilizing poetics in Olga Novo and Julieta Valero: against the institution of motherhood - Baños Palacios, Gema (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This article aims, from the reading of two recently published poetry books, Los tres primeros años by Julieta Valero (Vaso Roto, 2019) and Felizidad by Olga Novo (Olifante, 2020, Spanish translation by Xoán Abeleira), to open possible paths towards the representation of a radical feminine subjectivity that finds its anchorage in motherhood or, going further, in the contact full of gaps and fissures between mother and daughter. This link, from very different perspectives, favors and inaugurates a poetics in which the word unfolds in a necessary body to body, from an inner magma that does not constrain or repeat literary motifs, but, as already claimed by some French feminist thinkers such as Hélène Cixous, widen paths and invent worlds, precisely because they free themselves from the weight of a mostly male critical tradition that has relegated certain themes, such as motherhood, to a marginal role, detached from the central concerns of culture.